Can motivational interviewing be a helpful professional tool? Investigating teachers' experiences - Svensson, Martina; Wagnsson, Stefan; Gustafsson, Henrik (Educational research (Windsor), 2021)
Background: Motivational interviewing (MI) is a collaborative communication style used to enhance behaviour change, and there is increasing support for using MI in schools. However, little is known about school-based MI from a teacher perspective and how MI is applied by teachers in their daily work. Understanding teachers' use and experiences of MI could provide valuable information for future school development and teacher education. Purpose: This study aimed to explore teachers' experiences and perceptions of applying MI in Swedish compulsory schools (grades 1-9; 7-15 years). Methods: Interviews were conducted with 13 teachers, who taught different subjects in grades 4-9 (10-15 years). The teachers were from five schools in five different municipalities. They all had received a three- or four-day intensive training programme in MI. A qualitative content analysis approach was used to analyse the data. Findings: Our analysis indicated that teachers perceived MI to be a useful method that provided concrete tools to apply in their daily work. The teachers thought that MI facilitated their relational work, and helped them to become more guiding and autonomy-supportive than before. Hence, the teachers expressed a wish that MI should be included in teacher education. In addition, some teachers felt that MI could be effective in conflict management, to respond to pupils with challenging behaviour and to strengthen pupils' motivation, as well as in conversations with parents. However, teachers considered that lack of time was an obstacle to the application of MI in school and noted that MI requires ongoing training and continuity in order to be effective. Conclusions: This small-scale study draws attention to MI's potential as a supportive tool. Further research is needed to determine how far it may help teachers in a range of educational settings as they seek to foster collaborative relationships in school and facilitate relational work with their pupils.